PO025 Hepatitis e virus infection and acute non-traumatic neurological injury: an international prospective pilot study. (1st December 2017) - Webb, Glynn W; Dalton, Harry R; Eijk, Jeroen JJ van; Cintas, Pascal; Madden, Richie G; Jones, Catherine; Norton, Benjamin; Pique, Julie; Lutgens, Suzanne
Abstract : Background: Hepatitis E virus (HEV) is a common zoonotic infection associated with pigs which is endemic in many developed countries. Most infections are asymptomatic, with only a minority causing clinically evident hepatitis. Numerous extra-hepatic manifestations are associated with HEV, most commonly neurological injury. The aim of the study was to explore the relationship between HEV and acute neurological illness. Methods: 464 consecutive patients presenting to 4 centres in the UK, France and the Netherlands with acute non-traumatic neurological illnesses were prospectively tested for HEV by serology and PCR. Findings: 11/464 patients (2.4%) had evidence of current/recent HEV infection. Neurological cases in which HEV infection was found included neuralgic amyotrophy (n=3, all PCR positive); cerebrovascular event (n=4); seizure (n=2); encephalitis (n=1); and an acute combined facial and vestibular neuropathy (n=1). Symptoms of hepatitis were mild and no patients were clinically jaundiced. Interpretation: The 3 cases of HEV associated neuralgic amyotrophy had similarities with other previously described HEV-associated cases; all were middle-aged males with bilateral involvement of the brachial plexus. This observation supports a causal relationship between HEV and neuralgic amyotrophy. To further understand the relevance of HEV infection in patients with acute neurological illnesses, case control studies are warranted.